SELF-CARE ACTIVITY PREVENT COMPLICATION DIABETIC PATIENT IN PUSKESMAS SITOPENG CIREBON: SELF-CARE ACTIVITY CEGAH KOMPLIKASI PASIEN DIABETES DI PUSKESMAS SITOPENG CIREBON - Komarudin; Gita Sesaria, Tifanny (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Diabetic foot ulcer (DFU) is responsible for approximately 85% of all amputations performed in individuals with diabetes. Providing education and physical exercise based on Self-care Activities (SCA) aims to prevent complications in type 2 diabetes mellitus (DM) patients at Sitopeng Health Center. Self-care Activities (SCA) in diabetes entail actions individuals take to manage the condition, including examination and prevention. Objective: The objective was to enhance the knowledge and skills of patients in preventing and minimizing complications of type 2 DM, particularly diabetic foot wounds, through education on physical exercises based on Self-care Activities (SCA). Method: Direct education commences with administering a pre-test questionnaire to assess patient knowledge, followed by material presentation, blood pressure checks, blood glucose monitoring, and instruction on physical exercises based on Self-care Activities (SCA) for type 2 DM patients. Finally, a post-test questionnaire (DKQ-24) is administered. Results: Following participation in the community service, 85% of the participants experienced an increase in knowledge level and demonstrated proficiency in foot exercise skills. Conclusion: Type 2 DM patients in the Sitopeng Health Center catchment area exhibit improved knowledge and skills after engaging in community service activities, reflecting effective collaboration between service and educational institutions.